Servant Leadership dan Kepuasan Kerja terhadap Kinerja Karyawan di Lembaga Keuangan Non Bank Pontianak - Fahruna, Yulyanti (Fakultas Ekonomi dan Bisnis, UNTAN, 2016)
This research aims to assess and obtain empirical evidence by testing different response toward servant leadership, job satisfaction on the performance of employees in non bank financial institutions of Pontianak. Non probability sampling technique in the form of purposive sampling is applied. The study was conduct 100 respondents, consist of 50 employees of PT. Pegadaian (Persero) Area Pontianak and 50 employees of PT. Finansia Multi Finance Pontianak. The result shows that among PT. Pegadaian (Persero) Area Pontianak and PT. Finansia Multi Finance Pontianak there is a difference in case of servant leadership, job satisfaction and performance of employees where as the similarity between both non bank financial institutions on Pontianak.